Pengembangan UMKM Dengan Pembuatan Daftar Menu Menarik dan Banner di Desa Pasinan Kecamatan Lekok Kabupaten Pasuruan - Rizma Melina Oktabian Alifani; Nadifa Salsabilah; Alfina Rahma; Mila Hariani; Rommy Hardyansah; Misbachul Munir; Jahroni Jahroni (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Community service is a form of implementation of the Tri Dharma of Higher Education, with the aim of having a positive impact on society. This activity was carried out on 29 July 2024 in Pasinan Village, Lekok District, Pasuruan, with a focus on developing local Micro, Small and Medium Enterprises (MSMEs). The Unsuri team collaborated with MSME players in designing marketing strategies through attractive menu list and banner designs. The approach used is participatory, where MSME players are actively involved in every stage of planning. The methods used include field observations, interviews, design, and implementation of marketing strategies based on the results of MSME needs analysis. Active participation from villagers is expected to increase programme engagement and sustainability, as well as strengthen the competitiveness of local products. The results of this programme show an increase in the visual appeal and professional image of MSMEs, which has a positive impact on sales potential and the village economy.